Architectural Missionary : D. Fred Charlton in Michigan's Upper Peninsula, 1887-1918 - Brisson, Steven C. (Steven Charles), 1967- (Book collections on Project MUSE., 2021)
"In 1890, D. Fred Charlton opened his own office, becoming the first professional architect to reside permanently in Michigan's Upper Peninsula. Over the next twenty-eight years, he designed buildings throughout the region. The book covers the evolution of the Charlton's office during the period when architecture was evolving into a profession, something he championed"--